The Utilization of Jamu Waste as a Biofertilizer Material for Making Organic Fertilizer in Rukun Makaryo Farmers Group - Sulistyaningsih, Catur Rini; Handayani, Catur Budi (International Journal for Educational and Vocational Studies, 2020)
The Community Partnership Program aims to handle livestock waste, namely the making of starter-mol (biofertilizer) based on herbal waste as well as biological fertilizer and the manufacture of solid organic fertilizer based on solid manure (feces) and cattle feed residues. The target of the Community Partnership Program is to reduce waste pollution, especially herbal medicine waste, increase the added value of herbal waste that can be used as a source of microorganisms in making starter-mol (biofertilizer), increase knowledge about making biofertilizers and quality organic fertilizers, produce quality organic fertilizers in order to fulfil the fertilizer needs of Rukun Makaryo farmer group. Increasing the yield of organic rice produced by Rukun Makaryo farmer groups. The method is done by counseling with lectures, discussions, through training with direct practice by partners, mentoring to partners and evaluation. The 38 participants who followed the pretest-posttest and 57.63% improved understanding so that training and extension activities have reached an indicator of successLaboratory analysis results on the content of macroelements (N, P, K), organic C, organic matter and C / N Ratio following fertilizer quality standards from Menpen (Compost Standardization No: 28 / Permentan / SR.130 / 5/2009 , May 22, 2009 and 2005.